The Death of Self-Sadness in The Poetry of Khalil Mutran - عچرش, خیریة; برحي, ولید (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The motif appeared in the western cultural circles, and after many studies have proliferated in these circles, it has expanded its scope in the literature of other nations. It has deep roots in the phenomenon of repetition, a phenomenon that originated in Arabic rhetoric for centuries; means the main idea or theme and recurring concept effective in literary work. His appearance in literary production sheds light on the idea and crystallizes the motivation and motivation of the writer in his literary work; this is what helped the critics to reveal the code of literary works and the basic vision of their owners. In view of the life of the poet khalil matrun, and the pain and sadness that he had over his life, the motif of self-sorrow was created in his office, expressing khawalji and what goes around in his concerns, not involuntarily. With this exclusive method (Motif), we studied the sadness and pain of the poet and the suffering he suffered during his life, and the effect he had on his poetry. This study aimed at a descriptive_ analytical method to reveal the motive of self-sadness in the poet`s poems and to show his atmosphere and psychological struggle.